Increased Suppressor Activity of Ex Vivo Transformed Regulatory T Cells in Comparison with Unstimulated Cells of the Same Donor - Blinova, V. G.; Gladilina, Y. A.; Eliseeva, D. D.; Lobaeva, T. A.; Zhdanov, D. D. (Biochemistry (Moscow). Supplement. Series B, Biomedical chemistry, 2022)
— Regulatory T cells CD4 + CD25 + FoxP3 + СD127 low (Tregs) play a key role in the maintenance of tolerance to autoantigens, inhibit the function of effector T and B lymphocytes, and provide a balance between effector and regulatory arms of immunity. Patients with autoimmune diseases are characterized by decreased Treg numbers and impaired suppressive activity. Replacement therapy with autologous Tregs transformed ex vivo could restore the destroyed balance of the immune system. We developed a method for the cultivation of Treg precursor cells. Using this method, we were able to grow up to 300−400 million Treg cells from 50 mL of peripheral blood during a week. In this study, we demonstrated that 90−95% of ex vivo-transformed Tregs had the phenotype CD4 + CD25 + FoxP3 + СD127 low and increased the transcription of the FoxP3 and Helios genes. Ex vivo-transformed Tregs were characterized by increased demethylation of the FoxP3 promoter and activation of the proliferation gene markers cyclin B1, Ki67 and LGALS 1. Ex vivo-transformed Tregs had increased suppressive activity, and up to 80–90% of these cells secreted the cytokines TNFα and IFNγ. Our data suggest that ex vivo-transformed autologous Tregs have genetic, immunophenotypic and functional characteristics of regulatory T cells. In the future, they can be used for adoptive immunotherapy of autoimmune diseases and inhibition of transplantation immunity.